KNOWLEDGE OF ABORTION IN INDUSTRIAL WOMEN WORKERS - Nanang Rudy Utantyo; Yusmahenry Galindra (Universitas Batam, 2021)
Abortion or abortion (Latin: abortion) is the cessation of pregnancy before 20 weeks of gestation which results in fetal death (Sujiyatini, 2011: 72 in Resty, 2012). According to the World Health Organization (WHO) estimates there are 20 million incidents of unsafe abortion (Unsafe Abortion) in the world, 9.5% of which occur in developing countries. Approximately 13% of the total women who have an abortion who have an unsafe abortion end in death (Soetjiningsih, 2004 in Resty, 2012). Method : This study used a descriptive study. The population in this study were all female industrial workers who lived in the Batamindo Muka Kuning Dormitory at RW 03, totaling 1854 people and a sample of 185 respondents. Sampling in this study used the Consecutive Sampling technique, inclusion and exclusion criteria. The research was conducted in May-August 2017. The results were analyzed by Univariate. Result :Research Results Most of the respondents had less knowledge about abortion in female industrial workers at Dormitory Batamindo Muka Kuning Rw 03 Batam, as many as 127 (68.6%) of respondents. Conclusion : Based on the results of research conducted on 185 respondents, the following results were obtained: Most of the respondents had less knowledge about abortion in female industrial workers at Dormitory Batamindo Muka Kuning Rw 03 Batam, as many as 127 (68.6%) respondents. Suggestion As a source of information so that people can understand knowledge about abortion and be able to have a positive attitude towards social interactions.